The Death of Nuance and the Rise of the Affective: Political Elections in the Virtual Dark: / - Jevtić, Milica (Political Life, 2025)
Vukelić Miloš (2024) „Postdigitalni kulturni ratovi na zapadu“ Novi Sad: Akademska knjiga